Cognitive Bias and the Quality of Managerial Strategic Decision-Making Senior PTPN VI in Jambi Province: An Experimental Study of Overconfidence and Anchoring Effect in FFB Price Decisions and Plantation Expansion - Rodiana Rodiana (PT. Anagata Sembagi Education, 2026)
The quality of strategic decision-making is one of the factors that determines an organization's success in facing a dynamic and uncertain business environment. In the palm oil plantation industry, decisions regarding Fresh Fruit Bunch (FFB) pricing and plantation expansion are often influenced by various economic, regulatory, and managerial factors.PTPN VI manages more than 80,000 hectares of oil palm and rubber plantations and partners with thousands of smallholders, operating in an increasingly complex environment due to global CPO price volatility and regulatory pressures from the EU Deforestation Regulation (EUDR) 2023. The study used a mixed-methods design with a sequential explanatory approach, involving 60 senior managers from five units and divisions of PTPN VI Jambi through a decision scenario experiment based on actual data for the 2019-2024 period and a qualitative think-aloud protocol. Five hypotheses were formulated to test: (1) the effect of overconfidence on projection accuracy; (2) the effect of the anchoring effect on the quality of investment decisions; (3) the moderating role of cognitive diversity in the top management team (TMT); (4) the conditions for moderation effectiveness; and (5) the effectiveness of the behavioral debiasing protocol. The results are expected to produce a specific cognitive bias profile, empirical evidence of TMT moderation, and a contextual debiasing protocol that can be immediately implemented in the RKAP cycle and PTPN VI strategic meetings